Designing A Collaborative Learning Classroom In UNIMAS - Felicia Loo, Ragai (Universiti Malaysia Sarawak (UNIMAS), 2018)
Collaborative learning is not something new, but it has been the trend, it is to have an environment where the students would be able to work and communicate together in a small group to reach a goal. But the classrooms today still do not support collaborative learning, let alone enough facilities to enhance learning, hence the difficulty to have dialogue and to communicate freely. The aim of this study is to design a classroom that can support collaborative learning at a higher education level. Six students and two lecturers were interviewed to obtain their requirements for a collaborative learning classroom. A 3- Dimensional prototype design was produced based on their requirements. This prototype was then further improved based on the feedback by a classroom design expert.